Pengaruh Problem Based Learning (PBL) terhadap Hasil Belajar IPA Siswa Kelas VIII SMPN 1 Teras, Boyolali Semester Genap Tahun Ajaran 2015/2016 - Handayani, Desi, Dra. Hariyatmi, M.Si (2016)
Science education is a skill processing science, including product, process, scientific attitudes, facts, concepts, principles, laws, and theories. Science learning is the science process skills of observation, communication, clarification, measure, prediction, and summarize. PBL helping science education through observation, clarification, interpretation, prediction, implementation, planning a research, cooperation, critical thinking, and analytical. This research had purpose to understand the effect of PBL to the result of learning science VIII grade students of SMPN 1 Teras, Boyolali second semester of the 2015/2016 academic year. This research is kind of experimental research. Design of research used true experimental design that is Randomized Posttest Only Control Group by comparing the results of class learning with PBL and without it PBL. Study result of science class that using PBL had average score 81.01 ± 5.14 higher than class without PBL that only had average 77.22 ± 5.41. Based on hypothesis Independent Sample T-Test, the result of science learning had score Asymp.Sig value. 0,005 < constant of 0.05, so H0 rejected and Ha accepted. It is said there are differences in class learning with PBL and without PBL. Thus it can be concluded there was an effect of PBL concern to result of learning science VIII grade students of SMPN 1 Teras, Boyolali second semester of the 2015/2016 academic year.